Preparation of nanostructured zinc oxide thin film by electrochemical deposition method at different voltage/ Mohd Iqbal Ab Aziz - Ab Aziz, Mohd Iqbal (2010)
A study was conducted to prepare nanostructured zinc oxide thin film at different voltage by electrochemical deposition method. ZnO thin film was electrodeposited from an aqueous solution of Zn(NO)3 on indium tin oxide (ITO)-covered glass substrates. The depositions were carried out at -1.2 V, -1.3 V and -1.4 V while the time is keep constant at 5 minutes. Field emission transmission, Uv-Vis and X-ray diffraction measurements were performed to characterize the ZnO films. X-ray diffraction studies indicated that the obtained ZnO film were polycrystalline. The results showed that the films were presented different morphologies, grain size ranging from 180 to 320 nm. ZnO obtained at -1.3V and -1.4 V were compact and homogeneous and the variations in the band gap of ZnO films deposited under different conditions are also discussed.